2022
DOI: 10.1177/15248380211029405
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Gender-Based Violence Prevention and Response Interventions for HIV Key Populations: Female Sex Workers, Men Who Have Sex With Men, and People Who Inject Drugs

Abstract: Gender-based violence (GBV) is that perpetrated based on sex, gender identity, or perceived adherence to socially defined gender norms. This human rights violation is disproportionately experienced by HIV key populations including female sex workers (FSW), people who inject drugs (PWID), and men who have sex with men (MSM). Consequently, addressing GBV is a global priority in HIV response. There is limited consensus about optimal interventions and little known about effectiveness. Our systematic review followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Interventional approaches are needed to prevent and respond to diverse key HIV populations and identify priority areas for further development, rigorous evaluation, and implementation of evidence-based practices in priority areas. The intervention must include comprehensive prevention and response (Decker et al, 2022). The intervention was carried out to prevent transmission, which is embedded in HIV risk reduction and related health promotion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventional approaches are needed to prevent and respond to diverse key HIV populations and identify priority areas for further development, rigorous evaluation, and implementation of evidence-based practices in priority areas. The intervention must include comprehensive prevention and response (Decker et al, 2022). The intervention was carried out to prevent transmission, which is embedded in HIV risk reduction and related health promotion.…”
Section: Resultsmentioning
confidence: 99%
“…Each region must be alert and prioritize the HIV response and focus on key populations that are the most vulnerable (Fraser et al, 2021). Key populations are community groups at high risk of contracting and transmitting HIV due to factors that cause unsafe sex and the use of unsterilized injecting drugs (Decker et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the increased burden of poor mental health and substance use for transgender sex workers compared with their non-sex worker transgender peers may be the result of increased rates of interpersonal violence and sexually transmitted diseases seen in this subgroup. The creation of mental health and substance use services that specifically address violence experienced by sex workers and multi-level violence interventions may have a positive impact on reducing the prevalence of violence, poor mental health, substance use, and STIs [ 20 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simulation and modeling studies have found that reducing physical and sexual violence has the potential to avert up to 25% of incident HIV infections among WESWs, and up to 6% in the general population by decreasing condomless sex acts during sex work. 40 Multisectoral interventions that integrate community mobilization, empowerment, peer support, rapid crisis response, and relationship-based and individual-level HIV/STI risks factors such as alcohol use, harm reduction, and conflict de-escalation provide strong evidence of violence prevention in the context of HIV risk reduction 41 Among WESW in India, multi-level, combination approaches that integrate community mobilization, peer outreach, health and social services, social norms change, and individual as well as group counseling with intimate partners to improve trust, communication and self-efficacy have demonstrated efficacy 14 Improving economic conditions may also have the potential to reduce client violence in this population, and combination microfinance and HIV risk reduction interventions have been found to reduce violence and improve HIV risk behaviors in Kazakhstan and Mongolia. 4245…”
Section: Limitationsmentioning
confidence: 99%